Energy consumption, CO2 emissions and economic growth in developed, emerging and Middle East and North Africa countries. (15th July 2019) - Muhammad, Bashir
Abstract: The objective of this research is to examine the effect of economic growth, energy consumption and CO2 emissions on each other for a panel of 68 countries. I used panel data from 68 countries over the period 2001–2017 for developed, emerging and the Middle East and North Africa (MENA) countries. I applied seemingly unrelated regression (SUR) and dynamic models estimated through means of the generalized method of moments (GMM) and System generalized method of moments (Sys GMM) for data analysis. The estimated empirical results indicates that economic growth increase with increase in energy consumption in developed and emerging countries while declined in MENA countries; CO2 emissions increase in all countries due to increase in energy consumption. Energy consumption increase in all countries but economic growth increase in all countries except MENA due to increase in CO2 emissions. The CO2 emissions increase while the energy consumption decrease in developed and MENA countries but energy consumption increase and CO2 emissions decrease in emerging countries due to increase in economic growth. Based on the estimated results it is recommended that the policy maker in these countries should adopt such strategies that should focus to adopt environmentally friendly technologies to decrease the CO2 emissions. Highlights: Energy consumptions boost the economic growth in developed & emerging countries. Energy consumptions negatively effect on economic growth in MENA countries. CO2 emissions boost the economic growth in developed & MENA countries. Economic growth increases the energy consumption in emerging countries. Economic growth increases the CO2 emission in developed and MENA countries.